2012
DOI: 10.1186/2049-9957-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Providing financial incentives to rural-to-urban tuberculosis migrants in Shanghai: an intervention study

Abstract: BackgroundFinancial issues are major barriers for rural-to-urban migrants accessing tuberculosis (TB) care in China. This paper discusses the effectiveness of providing financial incentives to migrant TB patients (with a focus on poor migrants in one district of Shanghai using treatment completion and default rates), the effect of financial incentives in terms of reducing the TB patient cost, and the incremental cost-effectiveness ratio of the intervention.ResultsNinety and ninety-three migrant TB patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 24 publications
2
38
0
1
Order By: Relevance
“…Twelve studies presented patient or treatment supporters directed financial interventions (among then seven quasi-experimental studies), including monetary incentives 22,24,25,27,28,29,35,39,40,41 , a conditional cash transfer program 42 and economic support by voucher delivery 43 . Some studies 22,27,28,35 combined financial and non-financial interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies presented patient or treatment supporters directed financial interventions (among then seven quasi-experimental studies), including monetary incentives 22,24,25,27,28,29,35,39,40,41 , a conditional cash transfer program 42 and economic support by voucher delivery 43 . Some studies 22,27,28,35 combined financial and non-financial interventions.…”
Section: Resultsmentioning
confidence: 99%
“…It is very likely that the increase in the treatment completion rate of the present study was not as large as that of the aforementioned study because the patients in the present study were not a select non-adherent group. Wei et al (12) found that when poor, migrant patients with TB in a Shanghai district were given financial incentives, TB treatment completion rates significantly improved by 11% (from 78% to 89%). The use of modest incentives via a structured programme has been proven to improve the effectiveness of public health interventions conducted in poor, urban populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of cash incentives is controversial. (12)(13)(14)(15) In Tulsky et al's study, (15) homelessness, alcoholism and drug abuse were identified as reasons for poor adherence, and cash incentives were found to be more effective than non-cash incentives in improving treatment adherence in these patients. Nevertheless, like Bock et al, (7) we opted to use non-cash grocery vouchers instead of cash incentives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kadar cicir rawatan menurun secara signifikan sebanyak 11.0% (daripada 22.0% kepada 11.0%) dalam kumpulan intervensi, berbanding dengan hanya 1.0% (daripada 24.0% kepada 23.0%) dalam kumpulan kawalan (Wei et al 2012).…”
Section: Perbincanganunclassified